(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Reoviruses are non-enveloped viruses with segmented double-stranded RNA (dsRNA) genomes that are members of the Reoviridae family. These viruses may infect a wide range of hosts, including people, mammals, birds, and reptiles, and are widely known for their diversity and zoonotic potential. Bangladesh announced the first verified cases of Reovirus infection in humans in January 2025, which might be a public health concern. Five patients were confirmed to be infected with Reovirus. All exhibited mild to moderate symptoms, with full recovery observed in each case. Epidemiological analysis suggests a zoonotic origin, with potential transmission linked to exposure to raw date palm sap, a known reservoir for bat-borne viruses. The identification highlights the need for more monitoring, better diagnostic tools, and public health awareness, especially in rural regions where close animal-human interaction is more prevalent, even though the clinical results were not severe and not dangerous. Bangladesh Journal of Infectious Diseases, June 2025;12(1):181-184